A construção da identidade profissional docente a partir das histórias de vida de licenciandos em Matemática participantes do Programa Residência Pedagógica da UNILAB - Freitas, Bruno Miranda (2020)
The initial training of teachers in the country is mostly based on the technical and baccalaureate dimension without proper discussion and approximation about the school reality, in addition to not adequately considering the subjective aspects of the students and in their formative trajectory. Faced with this scenario, we ask: How do Life Stories build knowledge and teaching identity? What is the place of life stories in initial teacher education? This work was inserted in the universe of a qualitative investigation (MINAYO, 2004), being guided by the foundations and procedures of the (Auto) Biographical Research in Education. Its general objective is: To understand the construction of the professional identity of students of the Mathematics Degree course at the University of International Integration of Afro-Brazilian Lusophony - UNILAB from the life stories and the experiential and / or training learning carried out throughout the course. existential and formative trajectory. The specific objectives are: (i) to identify how the formative memories contributed to the construction of professional identity by systematizing the students' life stories as a structuring object that constitutes the initial training; (ii) reflect on the limits and possibilities of Supervised Internships and PRP in the contribution of the Teaching Professional Identity; and (iii) identify from the Life Stories in Training, the knowledge mobilized by the Supervised Curricular Internship and by the PRP with the students for the constitution of teaching identity. Theoretical contributions were made up of Tardif, Lessard and Lahaye (1991), Gauthier (1998), Pimenta (2005), Josso (2010), Pineau and Le Grand (2012), Delory-Momberger (2014), Ferrarotti (2014) Dominicé (2014a, 2014b, 2014c), Nóvoa (2014), Barguil (2016), Pimenta e Lima (2017) and Olinda (2018), among others. Our research focus is the Mathematics Degree Course at the University of International Integration of Afro-Brazilian Lusophony - UNILAB. The research subjects were eight students participating in the Pedagogical Residency Program who experienced a process of biography developed in the Reflective Biographical Circle - CRB, a research and training device developed by Olinda (2018). The narratives of themselves, woven collectively, make it possible to understand the process of teacher identity construction, since the practice of life stories is multiform and autopoietic. As approximation strategies, we use participant observation (GHEDIN; FRANCO, 2011) and document analysis. The students reported, at the CRB: memories of the school and its teachers, the relationship with the discipline of Mathematics in Basic Education and the knowledge constituted in their experiences under the Supervised Internship and the Pedagogical Residency Program. The results indicate that life stories, by rescuing aspects of their formative trajectory, contribute to the construction of knowledge and professional teaching identity.